PENGARUH PENGGUNAAN MODEL RME TERHADAP KEMAMPUAN PEMECAHAN MASALAH SEHARI-HARI MATERI PERKALIAN BILANGAN CACAH SISWA KELAS III SD - Handayani, Nonia; Hariandi, Ahmad; Gusmaulia Eka Putri, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students’ ability to solve real-life mathematical problems is an essential competency in elementary school mathematics learning, particularly in multiplication of whole numbers. However, many students still experience difficulties in understanding and solving contextual problems because learning often focuses on procedural calculation rather than conceptual understanding. This study aims to determine the effect of the Realistic Mathematics Education (RME) model on students’ real-life problem-solving ability in multiplication of whole numbers in third grade of elementary school. This research used a quantitative approach with a pre-experimental method employing a One Group Pretest–Posttest Design. The subjects of this study were 16 third-grade students. Data were collected through problem-solving test instruments administered before and after the implementation of the RME model. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed a significant improvement in students’ problem-solving ability after the implementation of the RME model. The mean score increased from 31.56 in the pretest to 64.44 in the posttest, with a significance value of 0.000 < 0.05. These findings indicate that the use of the Realistic Mathematics Education model has a significant effect on improving students’ real-life problem-solving ability in multiplication of whole numbers.